Patient's Perception of the Role of Gym Activity in Abdominal Wall Herniation in Adults: A Prospective Study - Prabir Boruah; Rabbani Mahmoud ElSayed Hassan Daoud; Dylan Viani Walsh; Natallia Kharytaniuk; Salim Fredericks; James Ryan; Asila Abdelatif; Nuha Birido; Thomas Noel Walsh (SpringerOpen, 2024)
Abstract Background Despite significant changes in healthcare, work practices, and leisure activity, the proposed precipitating factors for abdominal wall hernias have remained largely unchanged for almost two centuries. We aimed to investigate if there have been shifts in these factors over time by examining patients' perception of precipitating factors for abdominal wall hernia development. This study was conducted in the Royal College of Surgeons In Ireland Department of Surgery, Connolly Hospital, Blanchardstown, Dublin, where patients with abdominal wall hernias completed a questionnaire  . Results A total of 277 patients (mean age 55.7; 85.6% male) with abdominal wall hernia completed the questionnaire (66.1% inguinal; 10.8% umbilical; 6.9% paraumbilical; 10.5% epigastric; 3.2% incisional; 1.4% femoral, and 1.1% port-site). One hundred and twenty patients (43.3%) believed their hernia was due to lifting, 71 (25.6%) cited gym activity and 17 (6.1%) cited other sporting activities as the precipitating factor. Traditional factors - chronic cough and constipation - were cumulatively cited only by 11 patients (4.0%), while prostatic obstruction was not cited by any. Conclusion This study suggests that fitness pursuits may be an increasing contributor to the development of abdominal wall hernia. Greater attention should be paid to the proper use of gym equipment to minimise the risk of hernia development.